PREFIKS BAHASA MELAYU ISOLEK SEDANAU - Romadon, Sapari (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Abstract Malay isolects Sedanau abbreviated BMIS is one of the local languages â€‹â€‹in Indonesia, especially in the island Sedanau, District Bunguran West Natuna. Researchers interested in choosing prefixes contained in BMIS because it serves to form derived words that the sentence becomes clear. Research on the affixation particularly prefix BMIS researchers limited to three issues, namely the shape, function and meaning. Data used in the study BMIS that the data collected during the fieldwork involving several native speakers who are natives BMIS Malay Sedanau Island. In obtaining the required data, the researcher used interview techniques and techniques refer to Sedanau society. Based on the analysis of data that has been concluded, the prefix in BMIS discount affixes are seven forms of N-, pÉ™N-, bÉ™-, tÉ™-, and di-. BMIS function prefixes in the form of the verb, noun, adjective, and the word of numbers. Prefix in BMIS have multiple meanings, namely, performing or working, use or consume, create or produce, possess or have, mengahsilkan or remove, do the job on his own, wear or wear, use, may possess properties or characteristics, which do, in a state , unintentional, and suddenness. Keywords: Form, Function and Meaning Prefix. Â